GRIYA, PURI, DAN JERO, NAMA PERUMAHAN MASA KINI: PERSPEKTIF PERGULATAN IDENTITAS - I Putu Gede Suyoga (Jurnal PATRA, 2019)
Griya, Puri, and Jero are terms specifically used to name the dwellings of Balinese aristocrats, namely brahmana, ksatrya, and wesia. These three groups of people are the highest group of citizens in the social structure of traditional Balinese society, also called tri wangsa. This study aims to uncover the identity struggle with the use of the names of the residential groups of citizens of the tri wangsa or the Balinese aristocracy into the names of today's housing developed by developers in Bali. This qualitative study with an interpretive descriptive approach uses Bourdieu's structural generative theory and Foucault's knowledge-power relations in the analysis of primary data obtained from the field, and interviews with informants determined by purposive sampling and secondary data based. Data collection was carried out through literature study and interviews. The study's findings show that in Foucault's view, the use of the names of the traditional Balinese aristocrats' dwellings is a new articulation that has articulated an earlier truth claim that has been established for about six centuries. It is also inseparable from the struggle for economic capital, cultural capital, social capital, and especially symbolic capital. The struggle of various capital in Bourdieu's perspective with its various forms of conversion also becomes a struggle for identity in the field of social struggle through the realm of residential society in Bali today.